Pelatihan Kreativitas Tie-Dye dan Pembuatan Hand Bag untuk Kemandirian Ekonomi Penghuni Panti Arrahman Yogyakarta - Ida, Ida; Tjun, Lauw Tjun; Aryani, Dewi Isma; Mulyadi, Riki Himawan; Satwikasanti, Winta Tridhatu; Darmayanti, Tessa Eka (Universitas Nusantara PGRI Kediri, 2023)
The Arrahman Foundation, located in Yogyakarta, is a social foundation aiming to increase orphanage residents' independence through the entrepreneurship program. One of the efforts to increase the independence of the residents of the orphanage so that they can become entrepreneurs is to collaborate with the Faculty of Art and Design and the Faculty of Business Maranatha Christian University in collaboration with Duta Wacana Christian University to provide training in tie-dye technique, handbag, determining production cost, profit, and break-even analysis. The participants were 11 residents of the orphanage aged 19-22 years old, the majority were women and had a high school education. The training methods with explanation, demo, and hands-on methods. As a result, participants can produce the creation of tie-dye and handbag. The results of data collection through the questionnaire regarding the knowledge about production costs, profit, and break-even. The results of the Wilcoxon sign rank test method using SPSS, there are different knowledge before and after training, and the knowledge increase after training. The implication is participants can produce and understand the basics of cost and profit.